Studi Populasi dan Karakteristik Pohon Bertengger Celepuk Rinjani (Otus jolandae) di Beberapa Jalur Hutan Kemasyarakatan (HKM) Wanalestari Desa Karang Sidemen Kabupaten Lombok Tengah: Study On Population and Characteristics of Rinjani Scoop Owl (Otus Jolandae) Tree Perch in the Some Paths of Community Forest Wanalestari Karang Sidemen Village Central Lombok - Kornelia Webliana; Qashmal Dwi Harianto; Maiser Syaputra (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
Rinjani Scops Owl (Otus Jolandae) is an endemic fauna that is included in the family of owls that are found in several forests that have been in the boundary or in the ecosystem of Mount Rinjani. The latest report published by IUCN in 2016 on the Rinjani Scops Owl (Otus Jolandae) is included in the Near Threatened (almost threatened) category. The purpose of this research is to know the population and characteristics of the trees perched Rinjani Scops Owl (Otus Jolandae) in several public forest lines Wanalestari Karang Sidemen village, Central Lombok. The method used in this research is divided into preliminary studies and primary research, where preliminary studies have been a method of literary studies, interviews, and observations. Then the main research has the IPA (Index Point Of Ambudance) method, measurement Of environmental physical condition, and vegetation structure with single compartments. Analysis of the user data is quantitative and qualitative. Results showed that the total population of Rinjani Scops Owl (Otus Jolandae) across the observation line in Hkm Wanalestari amounted to 16 individuals with an density of population each between 0,76-1,27 ha. The tree of the perched Rinjani Scops Owl (Otus Jolandae) consists of six types, namely the Dadap (Erythrina variegata) tree, Jackfruit (Artocarpus Heterophyllius), Durian (Durio zibethinus), Pecan (Aleurites moluccanus), Randu (Ceiba pentandra) and avocado (Parsea americana). The height of the Tengger tree ranges between 5-9 meters, diameter between 31,4-76,6 cm, and an area of heading 31,7-113,4 m2. The average temperature of Rinjani Scops Owl (Otus Jolandae) habitat of 25.4-25.6 °C humidity 76,4-76,6% and light intensity ranged from 0.9-4.68 Lux. Key Words : Rinjani Scops Owl, Animals, Population, Characteristics of perched trees